The Optimal Management of Acute Febrile Encephalopathy in the Aged Patient: A Systematic Review - Fereshte Sheybani; HamidReza Naderi; Sareh Sajjadi (Interdisciplinary Perspectives on Infectious Diseases)
The elderly comprise less than 13 percent of world population. Nonetheless, they represent nearly half of all hospitalized adults. Acute change in mental status from baseline is commonly seen among the elderly even when the main process does not involve the central nervous system. The term “geriatric syndrome” is used to capture those clinical conditions in older people that do not fit into discrete disease categories, including delirium, falls, frailty, dizziness, syncope, and urinary incontinence. Despite the growing number of elderly population, especially those who require hospitalization and the high burden of common infections accompanied by encephalopathy among them, there are several unresolved questions regarding the optimal management they deserve. The questions posed in this systematic review concern the need to rule out CNS infection in all elderly patients presented with fever and altered mental status in the routine management of febrile encephalopathy. In doing so, we sought to identify all potentially relevant articles using searches of web-based databases with no language restriction. Finally, we reviewed 93 research articles that were relevant to each part of our study. No prospective study was found to address how should AFE in the aged be optimally managed.